História e transformação da Quadrilha Roceira Flor do Candorina de Curuçá - PA - RODRIGUES, Márcia Vitória de Carvalho (2018)
This work aims to investigate the history and transformation of the Bunch Flower Candorina City Curuçá -. Pa, since its foundation in 2003 until the year 2013 The research is a historical-descriptive-analytical survey of qualitative character. For this, it was necessary to historically contextualize the gang, recognizing the influence received from other dances, pointing out the general characteristics Mob Roceira then make the analysis and description of the history of the Flower Bunch of Candorina Curuçá - Para Theoretical Horizon is anchored the authors LEAL (2004), AMARAL (2012) and CHIANCA (2014). This study aims to contribute with other teachers and researchers.